Biobanking human endometrial tissue and blood specimens: standard operating procedure and importance to reproductive biology research and diagnostic development - Sheldon, Elizabeth; Vo, Kim Chi; McIntire, Ramsey A.; Aghajanova, Lusine; Zelenko, Zara; Irwin, Juan C.; Giudice, Linda C. (Fertility and sterility, 2011)
To develop a standard operating procedure (SOP) for collection, transport, storage of human endometrial tissue and blood samples, subject and specimen annotation, and establishing sample priorities. The SOP synthesizes sound scientific procedures, the literature on ischemia research, sample collection and gene expression profiling, good laboratory practices, and the authors’ experience of workflow and sample quality. The National Institutes of Health, University of California, San Francisco, Human Endometrial Tissue and DNA Bank. Women undergoing endometrial biopsy or hysterectomy for nonmalignant indications. Collecting, processing, storing, distributing endometrial tissue and blood samples under approved institutional review board protocols and written informed consent from participating subjects. Standard operating procedure. The SOP addresses rigorous and consistent subject annotation, specimen processing and characterization, strict regulatory compliance, and a reference for researchers to track collection and storage times that may influence their research. The comprehensive and systematic approach to the procurement of human blood and endometrial tissue in this SOP ensures the high quality, reliability, and scientific usefulness of biospecimens made available to investigators by the National Institutes of Health, University of California, San Francisco, Human Endometrial Tissue and DNA Bank. The detail and perspective in this SOP also provides a blueprint for implementation of similar collection programs at other institutions.